Collaborative Digital Marketing for Community Service to Support Promotion and Sales of Bogor City MSME Products with IBIK and UTHM: Pemasaran Digital Kolaborasi Pengabdian kepada Masyarakat untuk Mendukung Promosi dan Penjualan Produk UMKM Kota Bogor Bersama IBIK dan UTHM - Aang Munawar; Ani Mekaniwati; Budi Setiawan; Yulia Nurendah; Bambang H. Rainanto; Tarida Marlin; Anton Sukamto; Muanas; Adil Fadilah; Tri Marlina; Bambang Pamungkas; Sutarti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Digital marketing not only makes it easier for MSMEs to display their products to consumers but also expands their customer base. The limited knowledge of business actors, generally adults to old age, causes many businesses to experience setbacks and are forced to stop their business because they cannot compete in marketing. Therefore, training and assistance related to digital marketing need to be carried out to provide solutions for business actors so they can survive. This activity is a collaborative community service program between IBI Kesatuan (IBIK) with Universiti Tun Hussein Onn Malaysia (UTHM) and Bogor City MSMEs. The result of this activity is increased insight from business people regarding the use and use of digital platforms and other knowledge related to the requirements for selling products overseas.